On Ideals of Bi-Algebras - S. S Ahn; J. M Ko; Arsham Borumand Saeid (IndoMS, 2019)
In this paper, we discuss normal subalgebras in BI-algebras and obtain the quotient BI-algebra which is useful for the study of structures of BI-algebras. Moreover, we obtain several conditions for obtaining BI-algebras on the non-negative real numbers by using an analytic methods.